2007
DOI: 10.1038/nmeth1058
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant RNA technology: the tRNA scaffold

Abstract: During the past decades, RNA has emerged as a major player in most cellular processes.Understanding these processes at the molecular level requires homogeneous RNA samples for structural, biochemical and pharmacological studies. So far, this has been a bottleneck, as the only methods for producing such pure RNA were in vitro syntheses.Here, we describe a generic approach for expressing and purifying structured RNA in E.coli, using a series of tools which parallel those available for recombinant proteins. Our s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
238
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 211 publications
(245 citation statements)
references
References 31 publications
1
238
0
Order By: Relevance
“…It is known that RNA molecule is unstable in E. coli cells due to the rapid degradation caused by endogenous RNases. However, previous studies have shown that tRNA scaffolds can protect RNA from degradation (Normanly et al 1986;Ponchon and Dardel 2007). Taking this into consideration, we made three different structural constructs with Spinach, which are illustrated in Fig.…”
Section: Feasibility Test Using Spinachmentioning
confidence: 99%
“…It is known that RNA molecule is unstable in E. coli cells due to the rapid degradation caused by endogenous RNases. However, previous studies have shown that tRNA scaffolds can protect RNA from degradation (Normanly et al 1986;Ponchon and Dardel 2007). Taking this into consideration, we made three different structural constructs with Spinach, which are illustrated in Fig.…”
Section: Feasibility Test Using Spinachmentioning
confidence: 99%
“…A third method used to produce RNA for NMR studies was recently developed by Dardel and coworkers by producing RNA in vivo using a tRNA scaffold to protect the RNA from cellular RNases [121,122]. The tRNA scaffold can be removed either by DNAzymes or by sequence-specific RNase H cleavage [115,[117][118][119].…”
Section: Rna Synthesismentioning
confidence: 99%
“…One of the problems for in vivo RNA nanoconstruction is the rapid degradation of RNA. However, recent work suggests that degradation can be avoided by incorporating tRNA structures into the transcripts (Ponchon and Dardel, 2007).…”
Section: Nucleic Acids As Components For Synthetic Biosystemsmentioning
confidence: 99%
“…A similar approach is conceivable for other RNA-based nanodevices. As for in vivo production of RNAbased nanostructures, the tRNA-technique mentioned above may be of great use (Ponchon and Dardel, 2007). In general, however, it may not be straightforward to transfer DNAbased in vitro technology to RNA-based in vivo systems.…”
Section: Towards In Vivo Implementation Of Dna Nanodevicesmentioning
confidence: 99%